The efficiency of municipal property tax collection in Mozambican municipalities: An analysis of the role of human resource qualification in tax administration — a case study of the municipality of Nampula, Moçambique (Research, Society and Development, 2026)
This study aims to analyze the efficiency of the collection of the Municipal Property Tax (IPRA) in the Municipality of Nampula, focusing on the role of human resource qualification in tax administration. The specific objectives are: to identify the qualification level of the human resources involved in the administration of the IPRA in the Municipality of Nampula; to evaluate the main constraints faced in the collection of the IPRA; to analyze the relationship between the qualification of employees and the efficiency of the tax registration, assessment, and collection processes; to examine the mechanisms and strategies currently (STM) used in the collection of the IPRA; and to propose measures to strengthen the technical capacity of human resources in order to improve the efficiency of IPRA collection. This article analyzes the efficiency of the collection of the Municipal Property Tax (IPRA) in Mozambican municipalities, focusing on the role of human resource qualification in tax administration. The research adopts a qualitative approach, based on bibliographic review, document analysis, and a case study of the Municipality of Nampula. The results indicate that, despite the implementation of the Municipal Tax System (STM), challenges persist in its use, particularly related to the insufficient technical training of employees. It is concluded that the qualification of human resources is a determining factor for the efficiency of tax collection.